#TITLE_ALTERNATIVE# - Zakiyuddin R (NIM 123 03 001), Ahmad
Abstract: The development of geophysical technology was progressed very fast. One sector that was developed is geotomography. Geotomography became an important technique to observe the objects below the earths surface. One of several traveltime tomography inversion methods is wavepath eikonal traveltime inversion. This method was able to reconstruct two dimensional velocity structure with good result. To imaging wave-speed distribution vertically and laterally, this inversion method should developed in three dimensional medium. Forward modelling was done with eikonal equation calculation used finite difference method to yield traveltime difference on every grid point. Beside that, calculation of traveltime residual was done to up-date slowness model. Value of traveltime residual was back projected along wavepath were defined with source wavelet. After that, Simultaneous Iterative Reconstruction Technique (SIRT) method was used to up-date slowness model until smallest error was achieved. This inversion method was applied to three dimensional syntethic models which have 70 m x 70 m x 70 m dimension. This models were divided to 8 x 8 x 8 grid points with 10 m grid interval. The syntethic models were investigated include gradation model, Low Velocity Layer model, and High Velocity Layer model. From three syntethic models were investigated, this method was able to reconstruct Low Velocity Layer with the best result. Reconstruct model with this inversion method yield good reconstruction although use homogeneous initial model.